Analisis Interrelationship Infrastruktur, Foreign Direct Investment (FDI) dan Kesempatan Kerja di Indonesia - Rahmad Zul Efendi; Zul Azhar (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2020)
This study aim to analyze the interrelationship between infrastructure, Foreign Direct Investment and employment in Indonesia, The data used in this study  are secondary data from 2013 to 2018 in 32 provinces in Indonesia using panel data on the VAR method. The result show that there is no interrelationship between infrastructure and FDI in Indonesia, there is a interrelationship between employment opportunities and infrastructure in Indonesia and there is no interrelationship between FDI and employment opportunities in Indonesia